Treatment outcome of pneumonia and its associated factors among pediatric patients admitted to Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia - Adbela, Gebremariam; Abdurahman, Hanan; Hailu, Saba; Keneni, Mulualem; Mohammed, Ahmed; Weldegebreal, Fitsum (Frontiers in Pediatrics, 2024)
Background Pneumonia is the leading cause of morbidity and mortality among children worldwide. Despite its substantial impact, there exists a dearth of evidence regarding treatment outcomes and related factors, particularly within the Ethiopian context. This study endeavors to address these critical gaps by examining the treatment outcome of pneumonia among pediatric patients hospitalized in the Hiwot Fana Comprehensive Specialized University Hospital. Method A facility-based cross-sectional study was conducted on 204 children (≤14 years of age) diagnosed with pneumonia and admitted to the Hiwot Fana Comprehensive Specialized University Hospital. An interview using a structured questionnaire accompanied by a review of medical records was used to collect data from the parents/guardians. A binary logistic regression model with an adjusted odds ratio (AOR) and a 95% confidence interval (CI) was used to identify the associated factors with the outcome variable. Statistical significance was set at P < 0.05 in the multivariable analysis. Result Among the 204 children (≤14 years) included in the study, 119 (93.6%, 95% CI: 90.2–96.9) patients with pneumonia survived whereas 13 (6.4%, 95% CI: 3.1–9.7) died. Multivariable logistic regression analysis, after adjustments for potential confounders, revealed that children who had malnutrition (AOR = 3.5, 95% CI: 2.37–12.44), were unvaccinated (AOR = 3.41, 95% CI: 2.25–11.87), had altered mental states during admission (AOR = 4.49, 95% CI: 2.28–17.85), and had complicated types of pneumonia (AOR = 5.70, 95% CI: 2.98–15.09) were independently associated with mortality. Conclusion Poor treatment outcome was 6.4% among pediatric patients admitted with pneumonia in this study setting. Being unvaccinated, malnourished, and admitted with a complicated type of pneumonia as well as having altered consciousness at the time of admission were significantly associated with poor treatment outcomes. These findings underscore the critical need to prioritize preventative measures against malnutrition and unvaccinated status in children. Early identification of such children and proper interventions are imperative to reducing such outcomes, particularly in resource-constrained settings.